Remove or retain: ecosystem effects of woody encroachment and removal are linked to plant structural and functional traits. Issue 5 (22nd November 2020) - Eldridge, David J.; Ding, Jingyi
Summary: The impacts of woody encroachment and removal on ecosystems are highly variable and are thought to be related to the traits of the individual woody species. Decisions on whether to remove or to retain woody plants are hampered by a lack of empirical evidence of the relationship between woody traits and the ecosystem consequences of their removal or retention. We used a global meta‐analysis of 149 ecosystem attributes from 172 woody species to evaluate the relative effects of woody plant traits and abiotic environmental variables on the ecosystem consequences of woody encroachment and removal. The ecosystem consequences were closely related to woody plant traits. For example, encroachment of plants characterized by high structural traits (e.g. tall, mixed tap and fibrous roots) reduced ecosystem composition, while removal of plants characterized by high functional traits (e.g. nitrogen fixing, deciduous) reduced ecosystem function. Structural and functional traits of woody plants mainly regulated soil stability during woody encroachment and herbaceous cover after woody removal. Conversely, environmental conditions mainly affected herbaceous cover under encroachment and soil stability under removal scenarios. We demonstrate that the ecosystem consequences of encroachment and removal are closely linked to the structural and functional traits of the target woody species. Furthermore, biotic (woody plant traits) and abiotic (climate, soils) factors have different impacts on regulating trade‐offs between ecosystem responses under these two management scenarios. Our study provides empirical support for management decisions on whether to retain or remove different woody taxa under various environments across the globe.